Fall determinants in the adult Portuguese - Marques, Ana João (2020)
OBJECTIVES: Falls are a major public health issue, given its prevalence and social impact. This study aimed to (1) characterize fallers in the adult Portuguese population as well as (2) identify if some chronic conditions are fall determinants. MATERIAL AND METHODS: Our data of 7403 adults (≥18 years) was retrieved from phase 1 survey of EpiReumaPt, a representative sample of adult Portuguese population. We analyzed sociodemographic variables and the presence of chronic diseases, which was evaluated by self-report. Anxiety/depression symptoms were assessed using The Hospital Anxiety and Depression Scale (HADS). Fall was defined by the presence of a self-report fall in the previous 12 months to the interview. Univariate and Multivariable logistic regression were used to assess fall determinants. Analyses were conducted in Stata v13. RESULTS: The estimated prevalence of falls in the Portuguese population is 24,1%. Women are at 2.12 times higher risk of fall than man (95% CI 1.79 - 2.51) and there's also a progressive increasing association between age and falls, with people with 75+ years having greater odds of falling (OR = 1.86 95% CI 1.49 - 2.31). Different chronic health conditions were identified as major determinants of falls in the Portuguese population. Neurologic (OR = 1.64 95% CI 1.17 - 2.32) and rheumatic (OR = 1.44 95% CI 1.18 - 1.74) disease were significantly and independently associated with falls. Similar results were found for presence of anxiety (OR = 1.33 95% CI 1.04 - 1.71) or depression (OR = 1.61 95% CI 1.20 - 2.15) symptoms. CONCLUSIONS: Our results show a perspective of the determinants of falls in the Portuguese population, allowing us to know that women and elders are at greater risk. We have showed that some chronic diseases are associated with falls, in particular musculoskeletal diseases and mental diseases. Implementing specific and adapted prevention strategies might reduce the number and complications of falls ultimately improving Portuguese overall health.